Pengaruh Penggunaan Media Picsart Terhadap Kemampuan Menulis Teks Iklan Dengan Poster Siswa Kelas VIII MTs Nurul Huda Bangai - Mauzi Yopita Indriyani Siregar (Jurnal Pendidikan Indonesia (JOUPI), 2023)
This study aims to describe the effect of using Picsart Media on the ability to write advertisement text for class VIII MTs Nurul Huda Bangai. This type of research is quantitative research using an exsperimental model. The sample is this study were class VIII student of MTs Nurul Huda Bangai totaling 35 people. The data in this study werw the scores of writing skills of advertising text before using Picsart Media and the scores of writing skills after using Picsart Media for class VIII MTs Nurul Huda Bangai. The results of this study can be concluded that the results of the t-tes have the effect of using Picsart Media on the abality to write advertisement text in class VIII MTs Nurul Huda Bangai because tcount > t table (5,825 > 1,689)